Cryptocurrency investment intentions of generation Z - Yulfiswandi; Kenrick; Candy (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2026)
This study aims to analyze the influence of financial literacy, perceived risk, facilitating conditions, and social influence on behavioral intention, with attitude as a mediating variable. The sample consisted of 430 Generation Z respondents from Batam City, selected via convenience sampling, and the data were analyzed using Structural Equation Modeling (SEM) in SmartPLS. The results showed that financial literacy and social influence had a significant positive effect on attitude, whereas facilitating conditions had a significant positive effect on attitude but not on behavioral intention, and perceived risk did not significantly influence attitude. Attitude was shown to have a strong positive influence on behavioral intention. Financial literacy and social influence also had an indirect effect on behavioral intention through attitude, while perceived risk did not show a significant mediating effect. This study provides insight into the factors that influence behavioral intention and the important role of attitude as a mediating variable